The history and architecture of Al-Masjid Al-Haram - Spahic, Omer (Institut Terjemahan & Buku Malaysia (ITBM), 2018)
This book deals with the themes of the history and architecture of al-Masjid al-Haram. In the book, unless otherwise stated or implied, by al-Masjid al-Haram it is meant the Ka’bah and its immediate surrounding spaces and areas intended for facilitating the performing of religious rites and services, and by the Ka’bah it is meant only the Ka’bah (Baytullah or the House of God) itself, for such an itemization at present has become a customary and widespread approach, although in theory that is not necessarily always the case. The time-frame covered in the book is one commencing with Prophet Adam and ending with the first half of the era of the Ottoman Turks. The time-span covered in the book roughly ends with the first half of the era of the Ottoman Turks because what followed afterwards was an overture to a period of what could be described as a rapid disintegration and regression of Islamic homogeneous culture and civilization which ushered the Muslim world into the uncharted terrains of colonization, westernization and modernity. These, in turn, presented Islamic art, architecture and civilization as a whole with a great many unprecedented dilemmas and challenges which Muslims, unfortunately, are yet to fully come to terms with, let alone prevail over. The importance of the book lies in the fact that the history of al-Masjid al-Haram in many ways embodied the history and development of Islamic civilization. Moreover, on account of al-Masjid al-Haram phenomenon being an institutional marvel, a structure and an architectural space, it likewise embodied and reflected, to a large extent, the history and evolution of the identity of Islamic architecture. Concurrently with the development of al-Masjid al-Haram, Islamic art and architecture were also acquiring their trademark identities, breaking through and ultimately dominating the world cultural and civilizational scenes. It thus can be deduced that the three: al-Masjid al-Haram, Islamic civilization and Islamic architecture, were advancing together, one influencing, and being influenced by, the others. Studying thoroughly any one of them connotes studying a great deal of the other two as well. So integral and inter-reliant were they that irrespective of which one could be the cause and which one the effect, they – and indeed the whole Muslim community (ummah) with them -- are bound to rise and wane together. The book, it follows, offers some essential lessons on the theory, history and philosophy of Islamic architecture, as well as civilization, based on the colorful history and development of al-Masjid al-Haram. The book is divided into three chapters. In the first chapter, the origins and purpose of the Ka’bah and al-Masjid al-Haram is discussed. The chapter shows that due to the principle of inseparability between Islam, life, prophets and mosques – irrespective of the latter’s size and form -- as well as to the perpetual notions of the prayer, the qiblah (direction faced in prayers) and that of institutionalization of the conflicts between good and evil, a form of al-Masjid al-Haram, functioning as the first mosque on earth instituted for people, needed to exist as soon as during the time of Adam, the first man and prophet. Hence, prior to the epoch of Prophets Ibrahim and Isma’il, there existed Makkah sanctuary (haram) and the location as well as foundations of the Ka’bah (al-Masjid al-Haram), which had been instituted or appointed for humankind as early as when God created the heavens and the earth. As a result, the prophets before Ibrahim and Isma’il and their followers -- just like those who came after them -- were to face the place (the site of the Ka’bah, its foundations and the haram) in their prayers. When needed or commanded, a form of the pilgrimage (Hajj) to the place, too, was undertaken. Nonetheless, there is little disagreement about Prophet Ibrahim’s relationship with the Ka’bah and al-Masjid al-Haram: about building it and actualizing its projected status and function. This is so because the Qur’an and Prophet Muhammad’s Sunnah are at once explicit and eloquent as regards the subject matter, unlike the eras that preceded Prophet Ibrahim and the relationship between their own prophets and the Ka’bah. In the second chapter, the history of the Ka’bah and al-Masjid al-Haram from Ibrahim to Prophet Muhammad (pbuh) is presented. Building the Ka’bah by Prophets Ibrahim and Isma’il, and rebuilding it by Qusayy b. Kilab as well as the Quraysh tribe, is firstly dwelled on. Then, the role of the Holy Mosque during Prophet Muhammad’s time is thoroughly discussed under the subjects of the triumph of monotheism (tawhid) and the significance of the two qiblahs. Indeed, it was during Prophet Muhammad’s era that the seeds of both Islamic civilization and Islamic architecture – the latter in its capacity as a framework and physical locus of the former, as well as of the actualization of the Islamic message – were planted, and their first unmistaken manifestations came to pass. Finally, in the third chapter, the form and function of al-Masjid al-Haram from the time of Prophet Muhammad’s death, when the era of the rightly-guided caliphs (al-khulafa’ al-rashidun) commenced, till the rule of the Ottoman Turks, is discussed. This chapter most strongly illustrates a close relationship between the developments of the identities of each of Islamic civilization, Islamic architecture and al-Masjid al-Haram, one influencing the other, and one drawing on the strength of the other, regardless of which component exactly was the cause and which the effect in that intricate and relentless causal relationship.